Emerging therapies for AML with myelodysplasia-related changes: slowly but surely moving the needle. (3rd July 2021) - Phillips, Davis F.; Zeidner, Joshua F.
ABSTRACT: Introduction : Patients with acute myeloid leukemia with myelodysplasia-related changes (AML-MRC) have historically poor outcomes with conventional chemotherapy regimens. Current treatment strategies focus on intensive induction therapy followed by allogeneic stem cell transplant or a less intensive approach with hypomethylating agents with or without venetoclax. CPX-351 is a liposomal formulation of cytarabine and daunorubicin that has been shown to significantly improve response rates and survival compared with 7 + 3 (continuous infusion cytarabine plus anthracyclines). Despite the approval of CPX-351 for AML-MRC, overall prognosis remains poor with an unmet need to develop novel therapeutic strategies for this patient population. Areas covered : This article reviews the data for existing therapeutic options for patients with AML-MRC and the emerging therapies undergoing clinical trial development for this patient population. Expert opinion : The development of CPX-351 as a more effective induction therapeutic backbone for patients with AML-MRC presents an opportunity to investigate novel combination regimens in order to further improve outcomes. Promising emerging therapeutic modalities include immunotherapeutic strategies, small-molecule inhibitors and targeted agents. Unfortunately, there have been few clinical trials focusing on patients with AML-MRC with reliance instead on subgroup analyses. Clinical trials focused specifically on this patient population are urgently needed.